Gerry Smyth, Noisy Island: A Short History of Irish Popular Music (2005) - McCann, Anthony (Journal of the Society for Musicology in Ireland, 2007)
A review of Gerry Smyth, Noisy Island: A Short History of Irish Popular Music (Cork: Cork University Press, 2005), ISBN 1-85918-387-5, 190pp, €15/£13.95/$19.95.